Predictors of poor serologic response to COVID-19 vaccine in patients with cancer: a systematic review and meta-analysis. (September 2022) - Yang, Wenxing; Zhang, Dongxue; Li, Zhuo; Zhang, Kui
Abstract: Backgrounds: Patients with cancer presented a lower probability to obtain seroconversion after a complete course of COVID-19 vaccination. However, little was known on the factors that predict poor seroconversion in this frail population. Methods: We searched the PubMed, EMBASE, and China National Knowledge Infrastructure databases for all articles within a range of published years from 2019 to 2022 on the predictors of response to COVID-19 vaccine in patients with cancer (last search was updated on 2st March 2022). The odds ratio corresponding to the 95% confidence interval was used to assess the outcome. The statistical heterogeneity among studies was assessed with the Q-test and I 2 statistics. The review was registered with PROSPERO (CRD42022315687) and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Twenty cohort studies met the inclusion criteria for this study, with 5, 499 patients with cancer. We found that advanced age, male patients, and metastatic disease increased negative seropositivity to COVID-19 vaccine. Immunoglobulin heavy chain variable mutation status, high concentration of Ig G, Ig M, and Ig A were correlated with seropositivity. Relating to cancer treatment strategy, anti-CD20 therapy within recent 12 months and chemotherapy were negatively correlated with seroconversion. Meta-analysis found no significant difference associated with targeted treatment, immunotherapy, and endocrine treatment. Conclusions: Our meta-analysis assessed the factors that predict poor seroconversion in order to plan better prevention strategies in this frail population. The results proposed that enhanced vaccination strategies would be beneficial for the special patients such as advanced male, or patients receiving active chemotherapy, and carefully prevention should be emphasised even after a complete course of vaccination. Highlights: We assessed factors predicting seroconversion of COVID-19 vaccines in patients with cancer. Twenty cohort studies with 5, 499 patients with cancer were included in the current meta-analysis. IGHV mutation status and high levels of IgG/M/A are correlated with seropositivity. Chemotherapy and recent 1-year anti-CD20 therapy are correlated with seronegativity. Targeted treatment/immunotherapy/endocrine treatment does not affect seroconversion.